2022
DOI: 10.1177/22799036221135221
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prevalence of self-reports of Alzheimer’s disease/dementia among non-institutionalized individuals 45+ in Canada, 1994–2014

Abstract: Background: Alzheimer’s disease/dementia (AD) prevalence is of concern globally and in Canada owing to the rapidly aging population and increase in life expectancy. This study explored: (1) trends in the overall prevalence of self-reported AD/dementia by sex, age groups, educational levels, and geographic areas in Canada from 1994 to 2014, and (2) assessed what the observed trends mean in the context of the aging Canadian population and the health care system. Design and methods: This cross-sectional study use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Our findings are consistent with research demonstrating an increase in the prevalence of dementia in recent years in Canadian communities and institutions. A previous study by Chambers-Richards et al reported on the trends in dementia in non-institutionalized individuals from 1994 to 2014 in Canada [ 18 ]. Results of that study indicated an overall increase in dementia prevalence over the study period, with greater increases noted for females as compared to males in later years.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with research demonstrating an increase in the prevalence of dementia in recent years in Canadian communities and institutions. A previous study by Chambers-Richards et al reported on the trends in dementia in non-institutionalized individuals from 1994 to 2014 in Canada [ 18 ]. Results of that study indicated an overall increase in dementia prevalence over the study period, with greater increases noted for females as compared to males in later years.…”
Section: Discussionmentioning
confidence: 99%
“…With the worldwide growth of the elderly population, there has been a marked rise in cognitive disorders, including AD [7][8][9]. Future projections suggest a continued increase in AD cases, attributed to the global rise in life expectancy [7,9,10]. Data supports this projection, indicating that approximately 6.5 million Americans aged 65 and older were diagnosed with AD, with an expected growth in the number of older adults diagnosed with AD and related cognitive impairments [11][12][13].…”
Section: Socio-demographic Characteristics and Admentioning
confidence: 99%